Genome-wide analysis of chromatin packing in Arabidopsis thaliana at single-gene resolution - Liu, Chang; Wang, Congmao; Wang, George; Becker, Claude; Zaidem, Maricris; Weigel, Detlef

(untitled) (Genome Research, 2016)
The three-dimensional packing of the genome plays an important role in regulating gene expression. We have used Hi-C, a genome-wide chromatin conformation capture (3C) method, to analyze Arabidopsis thaliana chromosomes dissected into subkilobase segments, which is required for gene-level resolution in this species with a gene-dense genome. We found that the repressive H3K27me3 histone mark is overrepresented in the promoter regions of genes that are in conformational linkage over long distances. In line with the globally dispersed distribution of RNA polymerase II in A. thaliana nuclear space, actively transcribed genes do not show a strong tendency to associate with each other. In general, there are often contacts between 5′ and 3′ ends of genes, forming local chromatin loops. Such self-loop structures of genes are more likely to occur in more highly expressed genes, although they can also be found in silent genes. Silent genes with local chromatin loops are highly enriched for the histone variant H3.3 at their 5′ and 3′ ends but depleted of repressive marks such as heterochromatic histone modifications and DNA methylation in flanking regions. Our results suggest that, different from animals, a major theme of genome folding in A. thaliana is the formation of structural units that correspond to gene bodies.